2010
DOI: 10.2527/jas.2009-2218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial ruminal defaunation on urea-nitrogen recycling, nitrogen metabolism, and microbial nitrogen supply in growing lambs fed low or high dietary crude protein concentrations1

Abstract: Urea-nitrogen recycling to the gastrointestinal tract (GIT), N metabolism, and urea transporter-B (UT-B) mRNA abundance in ruminal epithelium were evaluated in partially defaunated (PDFAUN) and faunated (FAUN) growing lambs fed 2 levels (10%, low, or 15%, high) of dietary CP (DM basis). Four Suffolk ram lambs (43.9 +/- 1.4 kg initial BW) were used in a 4 x 4 Latin square design with 27-d periods. Sunflower oil was fed (6%; DM basis) as an anti-protozoal agent. Nitrogen balance was measured from d 22 to 26, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 47 publications
(87 reference statements)
7
31
4
Order By: Relevance
“…It is well established that defaunation consistently decreased NH3-N concentration (Kiran and Mutsvangwa, 2010). However, the result of NH3-N concentration obtained from this study was completely in contrast to those of the previous reports.…”
Section: Discussioncontrasting
confidence: 99%
“…It is well established that defaunation consistently decreased NH3-N concentration (Kiran and Mutsvangwa, 2010). However, the result of NH3-N concentration obtained from this study was completely in contrast to those of the previous reports.…”
Section: Discussioncontrasting
confidence: 99%
“…The dietary starch degradation in rumen was increased in defaunated sheep (Mendoza et al, 1993). There is a contrary between this experimental result and others (Kiran and Mutsvangwa, 2010;Grummer et al, 1983;Han et al, 1999;Mendoza et al, 1993), because before and after feeding ruminal acetate concentration was also increased by the protein supplementation ( Table 2). As the part of this study, the rumen digestible organic matter was unaffected by protein supplementation (Akhsan et al, 2015).…”
Section: Ruminal Fermentation Of Feed Carbohydratecontrasting
confidence: 45%
“…Kiran and Mutsvangwa (2010) (Grummer et al, 1983). Ruminal acetate and butyrate concentrations were decreased but propionate concentration was increased in defaunated sheep fed on high fiber diet (Han et al, 1999).…”
Section: Ruminal Fermentation Of Feed Carbohydratementioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, ruminal UT-B expression increases with age, correlating to increases in blood urea nitrogen (Naeem et al 2012) and it has recently been shown to be upregulated by solid feed intake (Berends et al 2014). In addition, UT-B mRNA expression increases in defaunated rumen, potentially explaining the increase in urea recycling that enables new microbial growth (Kiran and Mutsvangwa 2010). In adult cattle, bovine ruminal UT-B protein abundance and precise localization within the papillae cellular layers are regulated by dietary intake (Simmons et al 2009).…”
Section: Introductionmentioning
confidence: 98%